EVALUATION OF THE IMPLEMENTATION OF SELECTED GUIDANCE SERVICES IN SENIOR HIGH SCHOOLS IN THE SAGNARIGU MUNICIPALITY-GHANA - Asamari, A. A. (UDS International Journal of Development, 2019)
The study was carried out in Senior High Schools in the Sagnarigu Municipality of the Northern region of Ghana. The study examined the extent to which orientation, counselling and information services were implemented and perceived by male and female students. The study adopted the survey research design. Simple random and proportional representation methods were used to select a sample size of 480 students comprising 304 boys and 176 girls who responded to a questionnaire. Three research hypotheses were tested using t-test with an alpha level of 0.05. Results from the descriptive statistics revealed that students strongly agreed that orientation and counselling services were implemented in their respective schools. Regarding the hypotheses, the study found that there was no significant difference in the perception of male and female students towards the implementation of orientation, counselling and information services in the study schools. It is recommended that school authorities, Ghana Education Service and government should provide the needed resources and infrastructure for the effective implementation of the guidance services to address the needs of students. Besides, counsellors, teachers and parents should encourage both male and female students to patronise guidance services since the services could help them acquire good study habits and skills that can enhance their academic performance, among others. Keywords: Guidance, Senior High School, Students, Sagnarigu Municipality, Ghana.